Why didn't you tag me?!: Social exclusion from Instagram posts hurts, especially those with a high need to belong. (February 2022) - Büttner, Christiane M.; Rudert, Selma C.
Abstract: Humans are highly sensitive to ostracism experiences and thus, even very short occurrences of being excluded and ignored can threaten fundamental needs and lower mood. We investigated whether not being tagged causes similar negative responses as being excluded in real life. Using a multi-method approach, we show across five studies (total N = 1149) that not being tagged in a posted photo strongly threatens fundamental needs. This effect is moderated by individuals' need to belong, such that individuals with a higher need to belong experience not being tagged as more aversive. Results replicate across vignette studies in which participants imagine not being tagged on Instagram (Studies 2 and 3) and across studies using an alleged group task paradigm that mimicked the psychological mechanism of not being tagged outside of Instagram (Studies 4a and 4b). All experimental studies were pre-registered and we freely share all materials, code and data. Extending ostracism effects to the social media phenomenon tagging, the present research bridges real-world and digital social interactions. The results add to theoretical knowledge on social media, ostracism, and digital well-being and have practical implications for social media app design, social media interventions and our everyday interactions that increasingly happen online. Highlights: We investigate not being tagged as a novel form of ostracism on social media platforms (e.g., Instagram). Five studies (total N = 1149) show that not being tagged threatens fundamental needs. The aversive effects of not being tagged are stronger for individuals with a higher (vs. lower) need to belong. Findings from observational and vignette studies are solidified by experimental manipulations of (not) being tagged.